TEACHERS AS FACILITATOR TOWARDS REDUCING ANXIETY OF SECONDARY SCHOOL STUDENTS - Idris, Muhammad; Minaz, maksal; Khan, Dr. Shaista Irshad (Journal of Arts & Social Sciences, 2022)
The quantitative study was intended to compare the responses of female secondary school teachers with the responses of girl’s secondary school students regarding teacher as a facilitator towards reducing anxiety of secondary school students. The deductive research study was focused on research question; is there a significant difference among the responses of secondary teachers and students regarding the role of teachers in reducing anxiety. Aimed at this purpose all Secondary schoolgirls and female Secondary School Teachers (SSTs) of grade 9th and grade 10th in District Swabi were designated as the population of the study. The sample size of (164) female Secondary school teachers and girls students of class 9th and 10th were selected through convenient sampling technique by using Yamane Formula. Two Distinct questionnaires for the purpose of collecting data from female secondary teachers and Secondary schoolgirl’s were developed for the purpose of data collection. Research data were collected and analyzed by the help of SPSS 21. The data were analyzed by Mean, Standard Deviation as well as t-test was applied for the comparison. Results showed significant of difference between the responses of female secondary school teachers with the responses of girl’s students. Female teachers were more agreed with the statements that they help out the students in reducing anxiety as compare to the responses of girl’s secondary school student. It was recommended that professional development courses should be enriched related to reducing students’ anxiety.